Genome Sequence of Sphingobium yanoikuyae XLDN2-5, an Efficient Carbazole-Degrading Strain - Gai, Zhonghui (American Society for Microbiology, 2011)
Sphingobium yanoikuyae XLDN2-5 is an efficient carbazole-degrading strain. Carbazole-degrading genes are accompanied on both sides by two copies of IS6100 elements. Here, we describe the draft genome sequence of strain XLDN2-5, which may provide important clues as to how it recruited exogenous genes to establish pathways to degrade the xenobiotics.